PERANCANGAN SISTEM OTOMASI PADA SISTEM PENGKABUTAN BAHAN BAKAR DI PEMBANGKIT LISTRIK TENAGA GAS/UAP (STUDI KASUS DI UBP SEMARANG, PT INDONESIA POWER) - , RIFQI DWI PRABOWO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Atomizing air system is supporting unit in gas & steam power plant (PLTGU). This system means to increase the combustion efficiency by atomizing the fuel into fine mist. This will increase the surface of the fuel and causes complete combustion occures. Because of the importance of this, a system is needed in order to monitor and controlling the process of atomizing, the system is called automation system. The purpose of this research is to design an automation system on atomizing air system in gas & steam power plant (PLTGU). The design process is starting by analyzing the Process Flow Diagram (PFD) which given by PLTGU Tambak Lorok, UBP Semarang, PT Indonesia Power, then designing the Piping & Instrumentation Diagram (P&ID), specifying sensors and actuators, designing the architecture of automation system which is based on PLC SIMATIC S7-400, designing the Human Machine Interface (HMI), designing Functional Diagram and the last is programming PLC. The result of this research are the design of P&ID, the design of Functional Diagram which is based on standard document from ISA S5.1, the design of HMI which is based on standard document from ISA S5.5, specification of sensors & actuators also based on standard document form ISA S20 and the design of automation system architecture.